Conflicts of specific provisions and fundamental principles of labour relations regulation - Єрьоменко, В. В. (Theory and practice of jurisprudence, 2016)
This work investigates the following issues: problems of differentiation and application in practice of the fundamental principles of labour legislation and specific legal provisions, in particular, interpretation of the principles using legislative enactments; determination of legal principles and maxims of law; correlation of suprapositive law principles and principles embodied in positive law; possibility to deduce principles of legal regulation of labour relations from numerous provisions of labour legislation; ideas as to the mechanism of social effect of legal principles etc. The analysis of achievements in science, generalization of practice of enforcement of law, European and domestic experience, principles and methodology of scientific research allowed the author to admit that normative provisions of different level of generalization – from specific legal norms creating deep differentiation of legal regulation of labour relations and affect only limited circle of workers, to the fundamental principles of labour law having the highest level of generalization. Between these two poles there is a wide range of legal prescriptions which vary in the level of their generalization. To differentiate the fundamental principles and specific prescriptions of law on the basis of such criterion as a level of generalization of normative requirements worded there, is impossible because of ambiguity of this criterion. It is also impossible to use other substantial criteria for these purposes. Under such conditions there is only one alternative – to use a formal criterion. If a certain legislative provision is referred to as a fundamental principle in the Constitution or a legislative enactment it is applied as the fundamental principle including Part 7, Art.8 of the Civil Procedure Code and Part 7, Art.9 of the Code of Administrative Judicial Proceeding. In the rest of cases statutory provisions including the provisions of the highest level of generalization are applied as specific prescriptions of law.